nNOS-expressing neurons in the vmPFC transform pPVT-derived chronic pain signals into anxiety behaviors - Liang, Hai-Ying; Chen, Zhi-Jin; Xiao, Hui; Lin, Yu-Hui; Hu, Ying-Yi; Chang, Lei; Wu, Hai-Yin; Wang, Peng; Lu, Wei; Zhu, Dong-Ya; Luo, Chun-Xia (Nature communications, 2020)
Anxiety is common in patients suffering from chronic pain. Here, we report anxiety-like behaviors in mouse models of chronic pain and reveal that nNOS-expressing neurons in ventromedial prefrontal cortex (vmPFC) are essential for pain-induced anxiety but not algesia, using optogenetic and chemogenetic strategies. Additionally, we determined that excitatory projections from the posterior subregion of paraventricular thalamic nucleus (pPVT) provide a neuronal input that drives the activation of vmPFC nNOS-expressing neurons in our chronic pain models. Our results suggest that the pain signal becomes an anxiety signal after activation of vmPFC nNOS-expressing neurons, which causes subsequent release of nitric oxide (NO). Finally, we show that the downstream molecular mechanisms of NO likely involve enhanced glutamate transmission in vmPFC CaMKIIα-expressing neurons through S-nitrosylation-induced AMPAR trafficking. Overall, our data suggest that pPVT excitatory neurons drive chronic pain-induced anxiety through activation of vmPFC nNOS-expressing neurons, resulting in NO-mediated AMPAR trafficking in vmPFC pyramidal neurons. Chronic pain usually induces anxiety. Here, the authors report that vmPFC nNOS-expressing neurons are activated by excitatory inputs from pPVT during chronic pain and subsequently induce anxiety-like behaviors in mice through promoting AMPAR trafficking.